The Influence of Masculinity on Male Latino Adolescents' Perceptions Regarding Dating Relationships and Dating Violence. (July 2019) - Haglund, Kristin; Belknap, Ruth Ann; Edwards, Lisa M.; Tassara, Marcel; Hoven, James Van; Woda, Aimee
In the United States, teen dating violence (TDV) is a concern across ethnic groups. Attitudes and correlates of violence differ by gender, culture, and acculturation. This study used a qualitative interpretive approach. Data were obtained in focus groups with 23 Latino male adolescents. Themes reflected contexts of participants' lives, and definitions and nature of dating relationships and TDV. Participants described the importance of respecting dating partners, the destructive effects of TDV, and the pressure to display masculinity that can lead some young men to perpetrate TDV. These results may advance culturally relevant interventions to promote healthy relationships and prevent dating violence.